Learning Abdominal Imaging - Luna, Antonio; Vilanova, Joan C.; Ros, Pablo R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book is an ideal introduction to the use of radiology in imaging diseases of the liver, gallbladder and biliary system, pancreas, spleen, and gastrointestinal tract. Each of the ten chapters is devoted to a particular organ and contains ten illustrated case reports drawn from clinical practice. Common clinical situations and indications for imaging are reviewed, and clear descriptions are provided of the various imaging techniques that will assist in resolving diagnostic and therapeutic dilemmas. This book is recommended for medical students, residents, and inexperienced abdominal radiologists. Learning Imaging is a unique case-based series for thos in professional education in general and for physicians in particular.
Keywords: Medicine; Gynecology; Radiology, Medical; Gastroenterology; Clinical medicine; Urology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Gastroenterology; Hepatology; Urology/Andrology.; Gynecology